1970
DOI: 10.1042/cs0380613
|View full text |Cite
|
Sign up to set email alerts
|

Studies by Quantitative Immunoelectrophoresis on Iron Binding Proteins in Haemochromatosis

Abstract: 1. The concentrations of a number of plasma proteins in patients with haemochromatosis were determined by quantitative immunoelectrophoresis, particular attention being paid to the three iron transporting proteins.2. Transferrin and haptoglobin were within normal limits; haemopexin was significantly greater than normal (P< 0.001).3. Other changes observed were a significant (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1971
1971
1976
1976

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…A significant increase in this protein has previously been reported in patients with haemochromatosis (Amin, Clarke, Freeman, Murray-Lyon, Smith, and Williams, 1970), and in the discussion of their results these authors predicted that in other diseases with primary liver damage similar high concentrations would be found. The present study supports their surmise, but does not indicate whether the elevated serum levels reflect increased synthesis or decreased catabolism.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A significant increase in this protein has previously been reported in patients with haemochromatosis (Amin, Clarke, Freeman, Murray-Lyon, Smith, and Williams, 1970), and in the discussion of their results these authors predicted that in other diseases with primary liver damage similar high concentrations would be found. The present study supports their surmise, but does not indicate whether the elevated serum levels reflect increased synthesis or decreased catabolism.…”
Section: Discussionmentioning
confidence: 56%
“…The physiological role of %2-macroglobulin has not been defined and so the significance of the observed increase in serum levels in primary liver disease is obscure. Amin et al (1970) found a significant increase in fl1C/P1A levels in their patients with haemochromatosis. More recently Fox, Dudley, and Sherlock (1971) found normal concentrations of P,C/P1A in the majority of 150 patients with chronic liver disease, and in particular, normal levels were found in 30 patients with primary biliary cirrhosis, an observation consistent with our present results.…”
Section: Discussionmentioning
confidence: 88%
“…Since it is difficult to obtain pure standards for many individual proteins, use has been made of a pooled serum sample as the reference material, and results are expressed as 'per cent of reference serum'. Although this pool was obtained from normal blood donors, no claim is made that it represents normal values; the latter have already been defined by studying individual subjects relative to this standard pool (Clarke & Freeman, 1968). A single pool of antiserum made in goats, by using complete Freund's adjuvant, was used throughout this study.…”
Section: Methodsmentioning
confidence: 99%
“…Since at least forty individual serum proteins may be determined by this technique, the problem of identification is considerable. In the present study fifteen proteins have been identified by name, and a further five by numbers (Freeman & Smith, 1970). The nomenclature is given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Growing interest in the heme-binding serum protein hemopexin has recently developed in response to the observation that its concentration changes from the normal in a variety of diseases. A fall, reciprocal to plasma heme levels, is encountered in hemolysis (1)(2)(3) and in certain porphyrias (4 and our unpublished observations), and a rise in hemochromatosis (5), diabetes mellitus (6), and malignancies (7). Clinical Received for publication 20 June 1972 and in revised form 25 October 1972. in iron deficiency and the decrease in inflammatory reactions (8).…”
Section: Introductionmentioning
confidence: 99%